Comparison of baseline neuropsychological testing in amateur versus professional boxers - Bianco, M.; Ferri, M.; Fabiano, C.; Scardigno, A.; Tavella, S.; Caccia, A.; Manili, U.; Faina, M.; Casasco, M.; Zeppilli, P. (The Physician and Sportsmedicine, 2008)
The aim of the study is to investigate cognitive functions in boxers. The study population was composed of 2 groups of male boxers with no history of head concussions (except during boxing): a) 33 amateurs at their first examination; b) 27 professionals. Subjects were requested to: a) fulfill a questionnaire collecting demographic data, level of education, occupational status, boxing record (for professionals), and number of head concussions during boxing; b) undergo a computerized neuropsychological (NP) test (CogSport) measuring simple and complex reaction time (RT). Professionals were significantly (P < 0.0001) older (29.4 ± 4.19 years) and started boxing at a younger age (14.5 ± 3.94 vs 20.3 ± 4.77 years, P < 0.0001) than debutants (24.1 ± 5.13 years). Debutants showed significantly shorter simple RTs than professionals, both at the beginning (0.244 ± 0.007 vs 0.249 ± 0.007 s, P = 0.005) and the end (0.247 ± 0.007 vs 0.251 ± 0.008 s, P = 0.028) of NP test. Complex RTs did not differ between groups. Professionals showed a positive significant correlation between simple RT at the beginning of NP test and the total number of disputed (P = 0.043) and won (P = 0.035) bouts. In conclusion, professionals show a longer simple RT compared with debutants, with no difference regarding more complex cognitive tasks. A possible explanation may be found in an adaptation of skilled boxers to better (and longer) evaluate external stimuli before giving a motor response.